If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + 5q = 63 Solving 9p + 5q = 63 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5q' to each side of the equation. 9p + 5q + -5q = 63 + -5q Combine like terms: 5q + -5q = 0 9p + 0 = 63 + -5q 9p = 63 + -5q Divide each side by '9'. p = 7 + -0.5555555556q Simplifying p = 7 + -0.5555555556q
| 0=-9t | | 3(X+0.3)=1-X | | 3t+9t=20-10+26 | | 3x+14x-5=0 | | 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X | | -55+7=8n | | 4x+33=11x-30 | | 77-3x=33x+17 | | t+3+8(5+t)= | | X+6=0.5X-2 | | 11-9x=61-44x | | 3-28=5a | | 2x+35=5x+12 | | -114-8x=9x+22 | | 4(2X-7)=0 | | 9+5(t+1)+4t= | | 3x+7=-59-9x | | 10(2X-3)=8X | | 7(t+9)+5+t= | | 8t+(7+3t)4+2t= | | 4(X-1)=3(1-X) | | 7+9x=63+x |